Pushing the boundaries of innovation: the potential of ex vivo organ perfusion from an interdisciplinary point of view - Iske, Jasper; Schroeter, Andreas; Knoedler, Samuel; Nazari-Shafti, Timo Z.; Wert, Leonard; Roesel, Maximilian J.; Hennig, Felix; Niehaus, Adelheid; Kuehn, Christian; Ius, Fabio; Falk, Volkmar; Schmelzle, Moritz; et al. (Frontiers in Cardiovascular Medicine, 2023)
Ex Vivo Machine Perfusion (EVMP) represents an emerging technique for the preservation of explanted solid organs with primary application in allogeneic organ transplantation. Allowing for prolonged preservation and real time monitoring of organ quality while reducing/preventing ischemia reperfusion injury, EVMP has been established as an alternative to the standard of care static-cold preservation. Moreover, it has paved the way to involve expanded criteria donors, e.g., after circulatory death, thus expanding the donor organ pool. Ongoing improvements of EVMP protocols, especially expanding the duration of preservation, paved the way for its broader application, in particular for reconditioning and modification of diseased organs, as well as for tumor and infection therapies and regenerative approaches. Moreover, the implementation of EVMP for in-vivo-like preclinical studies improving disease modelling raises significant interest, while providing an ideal interface for bioengineering and genetic manipulation. These approaches can not only be applied in an allogeneic and xenogeneic transplant setting, but also in an autologous setting, where patients can be on temporary organ support while the diseased organs are treated ex vivo, followed by reimplantation of the cured organ.This review provides a comprehensive overview on differences and similarities in abdominal (kidney and liver) and thoracic (lung and heart) EVMP, focusing on the organ-specific components and preservation techniques, with a specific focus on the composition of perfusion solutions and their supplements, as well as on perfusion temperatures and flow conditions. Novel treatment opportunities beyond organ transplantation as well as limitations of abdominal and thoracic EVMP are delineated to identify complementary interdisciplinary approaches for application and development of this technique.